Polypropylene composition, preparation method and application
By selecting the appropriate component ratio and filler network among the polypropylene materials, the problem of high CLTE and density of polypropylene materials is solved, and a low-density and low CLTE polypropylene composition is realized, suitable for automotive lightweight designs.
Patent Information
- Application Number
- CN202510093478.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-21
AI Technical Summary
Due to its high linear thermal expansion coefficient (CLTE) and density, existing polypropylene materials are prone to dimensional problems when mated with metal parts in automobiles and are difficult to achieve lightweight design.
By selecting the appropriate component ratio, including homopolypropylene resin, POE resin, talc powder, hollow glass microbeads and nanofillers, a stable and complete filler network is formed, adjusting the rheological characteristics and phase morphology of the material, thereby reducing the density and linear thermal expansion coefficient of the material.
The low density and low CLTE of the polypropylene composition are achieved, suitable for automotive lightweight designs, and improve compatibility with metal components.
Smart Images

Figure BDA0005252231690000081 
Figure BDA0005252231690000082 
Figure BDA0005252231690000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a polypropylene composition, a preparation method and application. Background Art
[0002] Polypropylene is a cost-effective general-purpose plastic. After modification, it has excellent mechanical properties such as high strength and high toughness, as well as chemical resistance and high heat resistance. It is widely used in home appliances and automotive products.
[0003] With the development of automobile lightweight demand, the current amount of plastic used in automobiles can reach 300-400kg, and the amount of polypropylene is close to 40%. Due to its partial crystallization characteristics, the coefficient of linear thermal expansion (CLTE) of automotive polypropylene is about 120*10 -6 / ℃, so it has obvious thermal expansion and contraction characteristics, which leads to dimensional problems when it is matched with other parts, especially metal parts; at the same time, since traditional low-CLTE materials require a high filling ratio, the density of the prepared material is relatively high. Through further lightweight design, the density of the material is reduced and low-CLTE and low-density polypropylene materials are prepared, which is of great significance for the lightweighting of automobiles. Summary of the invention
[0004] The object of the present invention is to overcome the above-mentioned deficiencies of the prior art and provide a polypropylene composition having a relatively low coefficient of linear thermal expansion (CLTE) and a low density, a preparation method and an application thereof.
[0005] To achieve the above object, in a first aspect of the present invention, the present invention provides a polypropylene composition, wherein the polypropylene composition comprises the following components in parts by weight:
[0006] 38-62 parts of homopolymer polypropylene resin, 18-32 parts of POE resin, 13-27 parts of talc, 1-7 parts of hollow glass microspheres, 1-7 parts of nano filler;
[0007] The melt flow rate of the POE resin at a temperature of 190° C. and a load of 2.16 kg is ≥3 g / 10 min.
[0008] The polypropylene composition provided by the present invention can effectively reduce the density of the polypropylene composition by selecting components in appropriate mass parts and the components cooperate with each other, and the obtained polypropylene composition has a lower linear thermal expansion coefficient.
[0009] Specifically, homopolypropylene is used as the resin matrix, and talcum powder and nanofillers are selected for compounding. The two can be well dispersed in the resin matrix to form a stable and complete filler network, thereby effectively improving the overall dispersion uniformity of the material, and adjusting the rheological properties of the polypropylene matrix, which is beneficial to adjusting the phase morphology of the elastomer POE and helping to reduce the linear thermal expansion coefficient of the product; at the same time, the addition of POE resin in a suitable melt flow rate range can effectively avoid the formation of sea island structures, and is also beneficial to the stability of hollow glass microspheres and the regulating effect of hollow glass microspheres on the volume ratio of homopolypropylene and POE resin, thereby effectively reducing the density and linear thermal expansion coefficient of the product.
[0010] For example, the homopolymer polypropylene resin may be any point value or any two point range value between 38-62 parts, such as 40-60 parts, or 38 parts, 40 parts, 42 parts, 44 parts, 46 parts, 48 parts, 50 parts, 52 parts, 54 parts, 56 parts, 58 parts, 60 parts, 62 parts, etc.; the POE resin may be any point value or any two point range value between 18-32 parts, such as 20-30 parts, or 18 parts, 20 parts, 22 parts, 25 parts, 28 parts, 30 parts, 32 parts, etc.; the talc may be 13-27 The hollow glass microspheres can be any point value or any range value between 1-7 parts, such as 3-5 parts, or 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, etc.; the nanofiller can be any point value or any range value between 1-7 parts, such as 2-5 parts, or 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, etc.
[0011] Preferably, in the polypropylene composition, the mass percentage of homopolymer polypropylene resin is ≥34%.
[0012] More preferably, in the polypropylene composition, the mass percentage of homopolymer polypropylene resin is 40-56%.
[0013] It should be noted that the melt flow rate of the POE resin at a temperature of 190° C. and a load of 2.16 kg is obtained by testing with reference to ASTM D-1238:10.
[0014] As a preferred embodiment of the polypropylene composition of the present invention, the POE resin includes at least one of ethylene-butene copolymer and ethylene-octene copolymer.
[0015] As a preferred embodiment of the polypropylene composition of the present invention, the polypropylene composition comprises the following components in parts by weight: 45-50 parts of homopolypropylene resin, 23-27 parts of POE resin, 18-22 parts of talc, 3-4 parts of hollow glass microspheres, and 4-5 parts of nanofiller.
[0016] The present invention has found that the mass parts of the components in the polypropylene composition will also affect the performance of the product. When the mass parts of the components in the polypropylene composition are further selected to be within the above range, the comprehensive effect of the obtained product is better.
[0017] As a preferred embodiment of the polypropylene composition of the present invention, the homopolypropylene has a melt flow rate of 20-75 g / 10 min at a temperature of 230° C. and a load of 2.16 kg.
[0018] It should be noted that the melt flow rate of the homopolypropylene is obtained by referring to ASTM D-1238-2004 test, and the test conditions are temperature 230° C. and load 2.16 kg.
[0019] Exemplarily, the melt flow rate of the homopolypropylene at a temperature of 230° C. and a load of 2.16 kg can be any point value or any two point range values between 20-75 g / 10 min, for example, 21-73 g / 10 min, or 20 g / 10 min, 21 g / 10 min, 25 g / 10 min, 30 g / 10 min, 35 g / 10 min, 40 g / 10 min, 45 g / 10 min, 50 g / 10 min, 55 g / 10 min, 60 g / 10 min, 65 g / 10 min, 70 g / 10 min, 73 g / 10 min, 75 g / 10 min, etc.
[0020] Preferably, the homopolypropylene has a melt flow rate of 40-60 g / 10 min at a temperature of 230° C. and a load of 2.16 kg.
[0021] The present invention has found that the melt flow rate of homopolypropylene will affect the compatibility between components to a certain extent. When the melt flow rate of homopolypropylene is further selected to be 20-75g / 10min, especially 40-60g / 10min, the density and linear thermal expansion coefficient of the obtained product are lower.
[0022] As a preferred embodiment of the polypropylene composition of the present invention, the melt flow rate of the POE resin at a temperature of 190° C. and a load of 2.16 kg is 4-32 g / 10 min.
[0023] Exemplarily, the melt flow rate of the POE resin at a temperature of 190°C and a load of 2.16 kg can be a point value between 4-32 g / 10min or a range of any two points, such as 4-30 g / 10min, or can be 4g / 10min, 8g / 10min, 10g / 10min, 12g / 10min, 14g / 10min, 16g / 10min, 18g / 10min, 20g / 10min, 22g / 10min, 24g / 10min, 26g / 10min, 28g / 10min, 30g / 10min, 32g / 10min, etc.
[0024] Preferably, the melt flow rate of the POE resin at a temperature of 190° C. and a load of 2.16 kg is 13-18 g / 10 min.
[0025] The present invention has found that the melt flow rate of the POE resin affects the formation of the continuous phase of the product. When the melt flow rate of the POE resin is further selected to be 4-32 g / 10 min, especially 13-18 g / 10 min, the comprehensive performance of the obtained product is better.
[0026] As a preferred embodiment of the polypropylene composition of the present invention, the D50 particle size of the talc powder is 0.6-8.5 μm.
[0027] It should be noted that the D50 particle size of the talc powder is obtained by testing with a laser particle size analyzer with reference to GB / T 19077-2016.
[0028] Exemplarily, the D50 particle size of the talc can be any point value or any two point range values between 0.6-8.5 μm, for example, it can be 0.65-8 μm, 0.65-5 μm, or it can be 0.6 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, etc.
[0029] Preferably, the D50 particle size of the talc is 0.65-5 μm.
[0030] As a preferred embodiment of the polypropylene composition of the present invention, the hollow glass microspheres have a D50 particle size of 15-55 μm and a compressive strength of 1500-16500 psi.
[0031] It should be noted that the D50 particle size of the hollow glass microspheres is obtained by testing with a laser particle size analyzer with reference to GB / T 19077-2016, and the compressive strength is obtained by testing with isostatic pressure strength (water pressure method) with reference to JCT2284-2014 standard.
[0032] Exemplarily, the D50 particle size of the hollow glass microspheres can be any point value or any two point range values between 15-55 μm, such as 20-50 μm, 20-40 μm, or 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, etc. The compressive strength of the hollow glass microspheres may be any point value or any two point range value between 1500-16500psi, for example, 2000-16000psi, 8000-16000psi, or 1500psi, 2000psi, 3000psi, 4000psi, 5000psi, 6000psi, 7000psi, 8000psi, 9000psi, 10000psi, 11000psi, 12000psi, 13000psi, 14000psi, 15000psi, 16000psi, 16500psi, etc.
[0033] Preferably, the hollow glass microspheres have a D50 particle size of 20-40 μm and a compressive strength of 8000-16000 psi.
[0034] The present invention has found that the D50 particle size of the hollow glass microspheres will affect their dispersibility in the homopolymer polypropylene resin matrix, thereby affecting the density of the polypropylene composition; it will also affect the interaction between the hollow glass microspheres and the nanofiller and the talc powder, thereby affecting the overall compatibility, and further affecting the linear thermal expansion coefficient of the polypropylene composition; in addition, the D50 particle size and compressive strength of the hollow glass microspheres are also related to the stability of the hollow glass microspheres. When the D50 particle size and compressive strength of the hollow glass microspheres are further selected to be within the above range, the comprehensive performance of the obtained product is better.
[0035] As a preferred embodiment of the polypropylene composition of the present invention, the bulk density of the hollow glass microspheres is 0.15-0.4 g / cm 3 The packing density of the hollow glass microspheres is obtained by testing with reference to GBT 17431.2-2010.
[0036] As a preferred embodiment of the polypropylene composition of the present invention, the nanofiller has a dimension of 25-195 nm.
[0037] It should be noted that the nanofiller has a dimension of 25-195nm, which means that when the nanofiller includes a lamellar structure filler, the interlamellar spacing of the lamellar structure filler is 25-195nm; when the nanofiller includes a spherical particle filler, the D50 particle size of the spherical particle filler is 25-195nm; when the nanofiller includes a fibrous structure filler, the diameter of the fibrous structure filler is 25-195nm.
[0038] It should be noted that when the nanofiller is a spherical particle filler, the size of one dimension is obtained by testing with a laser particle size analyzer in accordance with GB / T19077-2016; when the nanofiller is a flaky structure filler, the size of one dimension is obtained by measuring with a scanning electron microscope; when the nanofiller is a fibrous structure filler, the size of one dimension is obtained by measuring with a scanning electron microscope.
[0039] Exemplarily, the size of one dimension of the nanofiller may be any point value or any two point range values between 25-195 nm, for example, 25 nm, 35 nm, 45 nm, 55 nm, 65 nm, 75 nm, 85 nm, 95 nm, 105 nm, 115 nm, 125 nm, 135 nm, 145 nm, 155 nm, 165 nm, 175 nm, 185 nm, 195 nm, etc.
[0040] Preferably, the nanofiller has one dimension with a size of 30-50 nm.
[0041] The present invention has found that when there is a dimension of the nanofiller within the range given by the present invention, it can better interact with talcum powder to form a complete structural network; at the same time, it can also better interact with hollow glass microspheres, thereby reducing the density and linear thermal expansion coefficient of the product.
[0042] As a preferred embodiment of the polypropylene composition of the present invention, the nano filler includes at least one of nano organic clay, nano titanium dioxide and nano silicon dioxide.
[0043] As a preferred embodiment of the polypropylene composition of the present invention, the polypropylene composition further comprises 0-1 part of a processing aid, and the processing aid comprises at least one of an antioxidant and a light stabilizer.
[0044] Illustratively, the antioxidant includes at least one of antioxidant 1010, antioxidant 168, antioxidant 1098, antioxidant 3114, and antioxidant 330; the light stabilizer includes at least one of UV-3808, UV-944, and UV-3853.
[0045] In a second aspect of the present invention, the present invention provides a method for preparing the polypropylene composition, the preparation method comprising the following steps:
[0046] (1) mixing a homopolymer polypropylene resin, talc and a nanofiller and then melt-extruding the mixture to obtain a one-step polypropylene composition;
[0047] (2) The first-step material of the polypropylene composition, the hollow glass microspheres and the POE resin are mixed and melt-extruded to obtain a polypropylene composition.
[0048] As a preferred embodiment of the preparation method of the present invention, in the step (1), the temperature of melt extrusion is 200-210°C, and the screw speed is 350-450r / min.
[0049] As a preferred embodiment of the preparation method of the present invention, in the step (2), the temperature of melt extrusion is 200-210°C, and the screw speed is 350-450r / min.
[0050] In the third aspect of the present invention, the present invention provides use of the polypropylene composition in preparing automobile devices.
[0051] Exemplarily, the automobile device includes any one of a dashboard, a door panel, a tailgate, and a bumper.
[0052] Compared with the prior art, the present invention has the following beneficial effects:
[0053] The polypropylene composition provided by the present invention can effectively reduce the density of the polypropylene composition by selecting components of appropriate mass parts, and the components cooperate with each other, and the obtained polypropylene composition has a lower linear thermal expansion coefficient. At the same time, the preparation method of the polypropylene composition provided by the present invention is simple to operate and is conducive to actual production. DETAILED DESCRIPTION
[0054] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0055] Unless otherwise specified, the reagents, methods and equipment used in the present invention are all conventional reagents, methods and equipment in the art; and unless otherwise specified, the raw materials used in parallel experiments are from the same batch of raw materials.
[0056] PP-1: homopolymer polypropylene, PP M60T, melt flow rate of 59 g / 10 min at 230 °C and load of 2.16 kg, Zhenhai Refining and Chemical;
[0057] PP-2: homopolymer polypropylene, HJ4045, melt flow rate 43 g / 10 min at 230 °C and load 2.16 kg, Korea Petrochemical;
[0058] PP-3: homopolymer polypropylene, MH20, melt flow rate 21 g / 10 min at 230 °C and load 2.16 kg, Lanzhou Petrochemical;
[0059] PP-4: homopolymer polypropylene, MN70, melt flow rate 73 g / 10 min at 230 °C and load 2.16 kg, Lanzhou Petrochemical;
[0060] PP-5: copolymer polypropylene, PP7935E1, melt flow rate 55 g / 10 min at 230 °C and 2.16 kg load, ExxonMobil;
[0061] POE-1: ethylene-octene copolymer, INFUSE 9807, melt flow rate of 15 g / 10 min at 190 °C and load of 2.16 kg, Dow Chemical;
[0062] POE-2: ethylene-octene copolymer, DF8200, melt flow rate 18 g / 10 min at 190 °C and load 2.16 kg, Mitsui Chemicals;
[0063] POE-3: ethylene-octene copolymer, ENGAGE 8137, melt flow rate of 13 g / 10 min at 190 °C and 2.16 kg load, Dow Chemical;
[0064] POE-4: ethylene-octene copolymer, ENGAGE 8407, melt flow rate 30 g / 10 min at 190°C and 2.16 kg load, Dow Chemical;
[0065] POE-5: ethylene-butene copolymer, ENGAGE 7447, melt flow rate of 4 g / 10 min at 190°C and 2.16 kg load, Dow Chemical;
[0066] POE-6: ethylene-octene copolymer, ENGAGE 8150, melt flow rate of 0.5 g / 10 min at 190 °C and 2.16 kg load, Dow Chemical;
[0067] Talc 1: HTPultra5 L, D50 particle size 0.65 μm, Italian, French;
[0068] Talc 2: AH-3000N9, D50 particle size 5 μm, Liaoning Aihai Yimi Mining Co., Ltd.
[0069] Talc 3: AH-1250N6, D50 particle size 8 μm, Liaoning Aihai Yimi Mining Co., Ltd.
[0070] Nanofiller 1: Nanoorganic clay, clay 20, fibrous structure, fiber diameter 30 nm, TOLSA, Spain;
[0071] Nanofiller 2: Nanosilica, HN-SP50, spherical particles, D50 particle size of 50 nm, Hengna New Materials Co., Ltd.;
[0072] Nanofiller 3: Nano titanium dioxide, CR-340, spherical particles, D50 particle size of 190nm, Pangang Vanadium Titanium Company;
[0073] Hollow glass microsphere 1: IM16K, D50 particle size 20 μm, compressive strength 16000 psi, 3M Company;
[0074] Hollow glass microsphere 2: HL50, D50 particle size is 40 μm, compressive strength is 8000 psi, Zhengzhou Shenglait Company;
[0075] Hollow glass microsphere 3: HL60, D50 particle size is 40 μm, compressive strength is 10000 psi, Zhengzhou Shenglait Company;
[0076] Hollow glass microsphere 4: HL32, D50 particle size is 50 μm, compressive strength is 2000 psi, Zhengzhou Shenglait Company;
[0077] Hollow glass microsphere 5: HL40, D50 particle size is 40 μm, compressive strength is 4000 psi, Zhengzhou Shenglait Company;
[0078] Solid glass microspheres: 050-40-A0, D50 particle size 40 μm, PG Company, USA;
[0079] Antioxidant: a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1, wherein antioxidant 1010 and antioxidant 168 are commercially available products;
[0080] Light stabilizer: UV-3808, commercially available.
[0081] Examples 1-18 and Comparative Examples 1-6
[0082] The embodiments of the present invention and the comparative examples provide a polypropylene composition, and the component contents (parts by weight) of the polypropylene composition are shown in Table 1-2;
[0083] Table 1
[0084]
[0085] Table 2
[0086]
[0087]
[0088] The preparation method of the polypropylene composition provided in Example 1 is:
[0089] (1) mixing a homopolymer polypropylene resin, talc and a nanofiller and then melt-extruding the mixture to obtain a one-step polypropylene composition; wherein the temperatures of the melt-extrusion zones are 190° C., 200° C., 200° C., 210° C. and 210° C., respectively, the screw speed is 400 r / min, and the screw aspect ratio is 40:1;
[0090] (2) The first-step material of the polypropylene composition, hollow glass microspheres and POE resin are mixed and melt-extruded to obtain a polypropylene composition; wherein the temperatures of the melt-extrusion zones are 190° C., 190° C., 200° C., 200° C., 200° C., 210° C. and 200° C., respectively, the screw speed is 400 r / min, and the screw aspect ratio is 40:1.
[0091] The preparation methods of the polypropylene compositions provided in Examples 2-18 and Comparative Examples 1-6 are consistent with that in Example 1, except that no relevant components are added. In Comparative Example 6, hollow glass microspheres are not added, but solid glass microspheres are added.
[0092] Effect example
[0093] The effect example of the present invention verifies the performance of the polypropylene composition prepared in the embodiment and the comparative example; the prepared polypropylene composition is injection molded, the injection molding temperature is 200°C, the original size of the injection molding sample is 100mm*100mm*3mm, and a small square of 10mm*10mm*3mm is cut for CLTE and density testing:
[0094] 1. CLTE test: refer to standard GB / T 36800.2-2018, test temperature range -30-100℃;
[0095] 2. Density test: Tested in accordance with standard ISO 1183-1:2012;
[0096] The test results are shown in Table 3;
[0097] Table 3
[0098]
[0099]
[0100] It can be seen from Table 3 that when the preparation method provided by the present invention is adopted, the obtained product has a lower density and linear thermal expansion coefficient; specifically, the linear thermal expansion coefficient of the obtained product is between 58*10-6 / ℃ or below, density is 1.037g / cm 3 the following;
[0101] It can be seen from Examples 1-3 and Comparative Examples 1-3 that the mass fraction of the components and whether a certain component is added have a certain influence on the performance of the product; when the hollow glass microspheres are not added in Comparative Example 1, the linear thermal expansion coefficient of the obtained product is significantly increased, and the density is also significantly increased; when the nanofiller is not added in Comparative Example 2, the linear thermal expansion coefficient of the obtained product shows a certain increasing trend; when talcum powder is not added in Comparative Example 3, the linear thermal expansion coefficient of the obtained product is significantly increased;
[0102] It can be seen from Example 1, Examples 4-6 and Comparative Example 4 that the type of polypropylene and the melt flow rate of homopolymer polypropylene also affect the density and linear thermal expansion coefficient of the product. When homopolymer polypropylene is not added in Comparative Example 4, the linear thermal expansion coefficient of the obtained product shows a certain increasing trend;
[0103] It can be seen from Example 1, Examples 7-10 and Comparative Example 5 that the melt flow rate of the POE resin affects the comprehensive performance of the product. When the melt flow rate of the POE resin in Comparative Example 5 is too low, the linear thermal expansion coefficient and density of the obtained product both show a significant increasing trend;
[0104] It can be seen from Example 1, Examples 13-16 and Comparative Example 6 that the particle size and compressive strength of the hollow glass microspheres will also affect the comprehensive performance of the product; when solid glass microspheres are used instead of hollow glass microspheres in Comparative Example 6, the linear thermal expansion coefficient and density of the obtained product are significantly increased.
[0105] Finally, it should be noted that the above embodiments are intended to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A polypropylene composition, characterized in that The polypropylene composition comprises the following components in parts by weight: 38-62 parts of homopolymer polypropylene resin, 18-32 parts of POE resin, 13-27 parts of talc, 1-7 parts of hollow glass microspheres, 1-7 parts of nano filler; The melt flow rate of the POE resin at a temperature of 190° C. and a load of 2.16 kg is ≥3 g / 10 min.
2. The polypropylene composition according to claim 1, characterized in that The polypropylene composition comprises the following components in parts by weight: 45-50 parts of homopolypropylene resin, 23-27 parts of POE resin, 18-22 parts of talc powder, 3-4 parts of hollow glass microspheres, and 4-5 parts of nano fillers.
3. The polypropylene composition according to claim 1, characterized in that The homopolypropylene has a melt flow rate of 20-75 g / 10 min at a temperature of 230° C. and a load of 2.16 kg.
4. The polypropylene composition according to claim 1, characterized in that The melt flow rate of the POE resin at a temperature of 190° C. and a load of 2.16 kg is 4-32 g / 10 min.
5. The polypropylene composition according to claim 1, characterized in that The D50 particle size of the talc is 0.6-8.5 μm.
6. The polypropylene composition according to claim 1, characterized in that The D50 particle size of the hollow glass microspheres is 15-55 μm, and the compressive strength is 1500-16500 psi.
7. The polypropylene composition according to claim 1, characterized in that The nanofiller has a dimension of 25-195 nm.
8. The polypropylene composition according to claim 1, characterized in that The polypropylene composition further comprises 0-1 part of a processing aid, wherein the processing aid comprises at least one of an antioxidant and a light stabilizer.
9. The method for preparing the polypropylene composition according to claim 8, characterized in that: The preparation method comprises the following steps: (1) mixing a homopolymer polypropylene resin, talcum powder and a nanofiller and then melt-extruding the mixture to obtain a one-step polypropylene composition; (2) The first-step material of the polypropylene composition, the hollow glass microspheres and the POE resin are mixed and melt-extruded to obtain a polypropylene composition.
10. Use of the polypropylene composition according to any one of claims 1 to 8 in the preparation of automobile devices.
Citation Information
Patent Citations
Low-density polypropylene compound filled with hollow glass beads and preparation method thereof
CN102492221A
Light-permeable polypropylene composition with good wear resistance and preparation method thereof
CN111073138A
Low-heat-storage-degree polypropylene composite material for automotive upholstery and preparation method thereof
CN112011123A
Scratch-resistant, low-thermal-conductivity and light-weight polypropylene composite material and preparation method thereof
CN117866338A
Polypropylene composite material as well as preparation method and application thereof
CN118388878A